Violência e cidadania na sociedade midiatizada: o programa Linha Direta sob a ótica da recepção - Lopes, Daniel Barsi (Universidade do Vale do Rio do Sinos, 2008)
The current investigation analyzes the relation between violence and citizenship in the contemporary society deeply trespassed by the phenom of mediatization taking as reference the TV show Linha Direta, aired every Thursday by Rede Globo de Televisão, since May, 1999. It presents theory and reflection about the research themes specially media, violence and citizenship, analyzed in an interrelated process and discusses the show detailedly, conjecturing about several elements of Linha Direta. The research is developed according to reception viewpoints, therefore focusing on the viewers and their interpretations from their contexts and experiences of the messages broadcasted, specially the ones concerning the configuration of a mediatized citizenship, acting in the struggle against the urban violence, and the relationship between Linha Direta and the State. The viewers that acted as informers for the research come from different scenarios and form three groups of investigation: Porto Alegre’s (RS) middle clas
Keywords: cidadania; investigação em recepção; Programa Linha Direta; violência; televisão; citizenship; reception investigation; television; violence; Ciências Sociais Aplicadas